Failure Mechanism and Structural Optimization of the Primary Support Structure for Expressway Tunnel in Soft Rock: A Case Study - Wu, Yamin; Duan, Junfeng; Xu, Jinfeng; Xu, Wanmin (Periodica polytechnica. Civil engineering. Bauingenieurwesen, 2024)
When the highway tunnel crosses the soft rock, the primary support structure often fails and damages because it cannot withstand the excessive surrounding rock pressure. For the Magu tunnel in Yunnan Province, which is in the upper hard and lower soft stratum, the surrounding rock deformation is large, and the primary support structure occurs spray concrete cracking, steel arch frame twisting deformation. According to the convergence constraint curve, this paper proposes to adopt the primary support optimization design scheme of "shortening the bench length + optimizing the length and arrangement of anchor rods". According to the numerical simulation results of FLAC3D, the important indexes such as deformation convergence, surrounding rock stress, anchor axial force and thickness of plastic zone in different excavation support conditions are analyzed. The conclusions are as follows: 1. The soft rock at the foot of the benches does not provide sufficient support resistance, resulting in large settlement and convergence deformation that can cause the primary support structure to fail and become damaged. 2. The length of the middle bench and the primary support strength and stiffness contribute most to the deformation. 3. The deformation control effect of the short anchor rods on the surrounding rock is relatively weak. Increasing the length of anchor can better play the role of anchor suspension enhancement and give full play to the surrounding rock's own bearing capacity. Finally, the deformation of the tunnel is under control after adopting the optimized primary support structure, which ensures the smooth construction.